2002
DOI: 10.1017/s1355770x02000025
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development in an aging economy

Abstract: In this paper, we analyze the effects of population aging on economic growth and the environment in a two-period overlapping generations model of growth, aging, and the environment. We show that aging may be beneficial to economic growth and the environment under perfect annuitisation, while possibly harmful under imperfect annuitisation. We also discuss the implications of our results for environmental policy in an aging economy.JEL Classification: J10, J14, O10, D62, D90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Jouvet, Phillippe, and Vidal (2000) construct an OGM model that includes a pollution externality in which individuals are altruistically linked to their offspring. Ono and Maeda (2001, 2002) analyze the effects of population aging on economic growth and the environment.…”
mentioning
confidence: 99%
“…Jouvet, Phillippe, and Vidal (2000) construct an OGM model that includes a pollution externality in which individuals are altruistically linked to their offspring. Ono and Maeda (2001, 2002) analyze the effects of population aging on economic growth and the environment.…”
mentioning
confidence: 99%
“…This formulation can be viewed in John et al (1995), Pecchenino and Pollard (1997), Maeda (2002), andOno(2002).…”
Section: Propositionmentioning
confidence: 99%
“…Focusing on those notions, they showed that whether aging is harmful to the environment depends on the curvature of utility function. Besides, Ono and Maeda (2002) further analyzed the effects of population aging on economic growth and the environment. They showed that the public annuity is a key factor in evaluating the effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Ono (2005) and Ono and Maeda (2001) who study the impact of increasing lifespan on the voted environmental policy, we model also the reverse effect that environmental quality has on longevity, while in these models lifespan is taken as exogenous. In common with these models of lifecycle savings and uncertain survival in the retirement period, we consider annuity markets to deal with savings left by predeceased agents (see also Pecchenino and Pollard 1997;Ono and Maeda 2002). By doing so, we are able to assess the effects of an improvement in the annuity markets' degree of completeness in terms of health expenditure, environmental quality, life expectancy and welfare.…”
Section: Literature Reviewmentioning
confidence: 99%